PENGARUH INSTITUTIONAL OWNERSHIP TERHADAP KINERJA PERUSAHAAN DIMODERASI DENGAN FAMILY OWNERSHIP PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Uliyah, Putri Ridhotul (Fakultas Ekonomi, 2022)
This study aims to examine the effect of institutional ownership moderated by Family ownership on the performance of companies listed on the Indonesian stock exchange.The sample of this research is manufacturing companies listed on the Indonesian stock exchange in 2014-2018, with a total sample of 81 companies. In this study, the data collection method used purposive sampling method with analytical tools using SPSS version 20. The results showed that (1) institutional ownership has a positive effect on company performance, calculated by Tobin`sQ (2) the moderating effect of Family ownership can weaken the positive influence of institutional ownership on company performance.Keywords : Performance, Institutional Ownership, Family Ownership, Size, Leverage